Oral presentation Contaminants on the Horizon: Bioprocess development for the treatment of ionic liquid-polluted industrial effluents - Vasquez Christodoulou, Marlen (My University, 2026)
Koutinas M, Pashali P, Loizou E, Nicolaou E, Vasquez MI, Vyrides I, Contaminants on the Horizon: Bioprocess development for the treatment of ionic liquid-polluted industrial effluents, Invited oral presentation M. Koutinas, New Horizons in Biotechnology (NHBT 2015), Trivandrum, India, 22-25 November 2015.